INFLUENCE OF SCALE ON THERMAL CHARACTERISTICS IN A LARGE MONTANE RIVER BASIN. (13th December 2011) - Imholt, C.; Soulsby, C.; Malcolm, I. A.; Hrachowitz, M.; Gibbins, C. N.; Langan, S.; Tetzlaff, D.
ABSTRACT This study monitored stream temperatures over two hydrological years at various nested scales within the large, unregulated river Dee catchment (North East Scotland). These scales were (i) the whole catchment (11 sites along main stem Dee); (ii) the tributary (single sites in main tributaries); (iii) the Girnock (five sites in one subcatchment); and (iv) the reach (26 points across single reach). The aim was to characterize the thermal regime of all locations and compare the magnitude of variation between each scale. The controls on this variation were assessed via a multiple linear regression model using Geographic Information System‐derived catchment data. Temperatures were collected at 15‐min resolution and for further analysis and discussion combined to daily means. At the catchment and subcatchment scales, a west to east gradient in mean and minimum temperatures was observed, largely paralleling changes in altitude. Temperature differences between subcatchments were generally greater than between the sites along the main stem of the Dee. Differences between tributaries reflected differences in their morphology and land use. However, some tributaries had similar thermal regimes, despite different catchment and riparian characteristics. Subcatchment differences in thermal regimes of one of the tributaries corresponded to riparian vegetation reduced diurnal variability in sections dominated by broadleaf woodland. Compared with the larger scales, reach differences in thermal regime were small (e.g. mean temperatures of riffle, pool and margin habitats were within 0.3°C). The most noticeable difference was in relation to the point samples within the backwater area, which has a more constant thermal regime, most probably reflecting its groundwater source. The regression analysis indicated that monthly mean temperatures can be predicted well using elevation and catchment area. Forest cover was a significant explanatory variable during the summer months. However, some of the empirical temperature data from the Dee indicate that similar thermal regimes can result from different physical controls and processes that have important implications for the extrapolation of such predictive models. Copyright © 2011 John Wiley & Sons, Ltd.